Analisis Pengendalian Kualitas Produksi Menggunakan Metode Six Sigma di Industri Ikan Asap UMKM Berkah Turah Kota Batang - Yulianto, Wildan; Suprijono, Herwin (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
This research was conducted at UMKM Berkah Turah, which is engaged in the smoked fish processing industry, with the aim of identifying and controlling product quality through the Six Sigma approach. The main problem faced is the high number of defective products, such as burnt fish, mushy meat texture, and uneven maturity. The Six Sigma method using the DMAIC (Define, Measure, Analyze, Improve, Control) approach was applied to identify the causes of the problem and formulate improvement solutions. The analysis results show that the main causes of defects come from human factors, traditional methods, non-uniform raw materials, uncontrolled environment, and inadequate tools. Based on DPMO data of 33,420 and a sigma level of 3.33, it is concluded that the production process is still within the control limits but requires further improvement to sustainably improve quality. Proposed improvements include increased worker supervision, use of modern smoking equipment, procurement of fresh fish raw materials from fishermen, and expansion of production space.